Marks i Bakunin w Pierwszym Międzynarodowym Stowarzyszeniu Robotników - Temkin, Hanna (Marx and Bakunin in the First International, 2007)
This article analyzes polemics between Marx and Bakunin during the International Workingsmen’s Association. The author presents these arguments as a conflict between two conceptions of the workers’ movement: centralist and federalist.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 203-238